Accelerated Aging as a Vigor Test in Encholirium spectabile Seeds - Ariana Veras de Araújo; Monalisa Alves Diniz da Silva; André Pereira Freire Ferraz (Floresta e Ambiente)
ABSTRACT The objective was to verify how differences in the accelerated aging test, traditional method (water) or saturated NaCl solution influence the differentiation of the physiological potential of Encholirium spectabile seeds from two geographic regions of Brazil (Graça-CE and Serra Talhada-PE). The experimental design was completely randomized in a 2 × 2 × 5 factorial scheme, in which two methods (water and saturated NaCl solution), seeds from two geographic regions and five aging periods (0 h, 24 h, 48 h, 72 h and 96 h) were evaluated. Results indicated that seeds from Graça-CE were less vigorous than those from Serra Talhada-PE. However, both aging methods (water and saturated NaCl solution) increased the physiological potential of seeds harvested from Graça-CE. E. spectabile seeds presented different levels of physiological potential by the accelerated aging test.